The importance of scientific competencies in German medical curricula - the student perspective - Ratte, Antonius; Drees, Simon; Schmidt-Ott, Tabea (BMC medical education, 2018)
Scientific competencies are of great importance for physicians; not only for conducting reliable research, but also for patient care. However, there is growing concern that a lack of scientific competencies among physicians may lead to a deterioration in the quality on biomedical research. This study aims at assessing medical students’ perspectives on the implementation of scientific competency training in German medical curricula.
Gesehen am 04.07.2018
Published online 19 June 2018